2022
DOI: 10.1155/2022/5851117
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Counseling for Headache OTC Medications in German Community Pharmacies Using a Simulated Patient Approach: Are There Differences between Self-Purchase and Purchase for a Third Party?

Abstract: Background. In Germany—as worldwide—headache is one of the most frequent causes of self-medication. The dispensing of over-the-counter (OTC) medications may only be carried out by community pharmacies (CPs). In doing so, CPs have to ensure “adequate” counseling, for both self-purchase and purchase for a third party, which also occurs in everyday pharmacy practice. The aim of this study was to evaluate the quality of counseling for headache OTC medications in German CPs and, as the first study worldwide, to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
(134 reference statements)
1
2
0
Order By: Relevance
“…Most of the male and female students took analgesics for headaches, this may be due to the stress of studying, Similar findings were in study carried out by Bernhard Langer et al, [11] however, the second complaint that led to selfmedication is the period pain (dysmenorrhea) for the female students.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the male and female students took analgesics for headaches, this may be due to the stress of studying, Similar findings were in study carried out by Bernhard Langer et al, [11] however, the second complaint that led to selfmedication is the period pain (dysmenorrhea) for the female students.…”
Section: Discussionsupporting
confidence: 80%
“…One of the reasons for this critique is that in a single contact with a CP, the service process of only one specific pharmacy employee can be observed and evaluated at a given time, whereby only one SP with certain characteristics can participate. Furthermore, the SP can either make a purchase for themselves (self-purchase scenario) or for a third party (purchase for a third-party scenario)[ 12 ]. Finally, the SP's demand may only include a specific product ( e.g., aspirin), condition ( e.g., migraine), or symptom ( e.g., headache) based on a corresponding simulated scenario[ 3 ].…”
Section: To the Editormentioning
confidence: 99%
“…Studies related to the provision of antipyretic analgesics for self-medication from community pharmacies have reported that the comprehensiveness of the information gathered, the appropriateness of the recommendations provided, and/or the adequacy of the counseling provided were sub-optimal. [10][11][12][13] In Indonesia, Lestari et al reported that only 9% of the 45 pharmacies in Lamongan district, East Java performed a patient assessment and only less than 10% of pharmacies provided medicine information related to the indication, how to use the medicines, and side effects when handling patients' request for mefenamic acid. 14 A study in Pekanbaru, Riau also showed similar results, in which only 24% of pharmacy staff performed patient assessment when responding to patients with toothache.…”
mentioning
confidence: 99%